French revolutionaries in the Ottoman Empire: diplomacy, political culture, and the limiting of Universal Revolution, 1792-1798 - Firges, Pascal (Oxford University Press, 2017)
An unusual view of the French Revolution as one of moderation and compromise, transforming not only the French state, but territories throughout the world. This volume focuses on its impact across the Ottoman Empire, shedding new light on the global repercussions of the French Revolution and on French revolutionary foreign politics and diplomacy